Effect of Urea Molasses Mineral Block Supplementation on Milk Production in Murrah Buffalo under Small holder’s Production System - Bipate, Mahesh (Indian Journal of Animal Nutrition, 2021)
The present study was conducted at farmer’s field in Muzaffarnagar district of Uttar Pradesh to assess the response of urea molasses mineral block (UMMB) supplementation on milk production and body condition score in buffaloes. Twenty Murrah buffaloes in early lactation stage were selected and divided into two groups of 10 each. Animals of T1 group were given free access to urea molasses UMMB for two-three hours in the morning in addition to their normal ration for eight weeks after adaptation period of two weeks. However, thebuffaloes in control (T0) group did not receive any supplement. The buffaloes were managed as per the standard feeding practices followed by the farmers. Significant increase in milk yield (P